(untitled) (Economic and Political Thought, 2016)
With one exception, Lord Acton did not write anything that is entirely devoted to Poland. On the other hand, the Polish Lithuanian Commonwealth and Poland in general are mentioned many times in his writing. The article collects those scattered remarks and attempts to explore Lord Acton’s views on Poland, beginning with Poland’s origins in the tenth century and ending with the January Uprising of 1863. The conclusions are somewhat disappointing and surprising. Knowing Polish history in detail, Lord Acton did not go beyond standard Western clichés about it, proving he did not reflect much on the nature of gentry’s democracy and Polish liberties. The most surprising of his views on the uprising, in turn, is his cold, realpolitik approach, far from his usual dogmatic love of civic liberty. In this respect, the article in a way revises what we have known so far about Acton’s theory of liberty and his view on liberalism.